Coupled Best Proximity Point Theorem for Generalized Contractions in Partially Ordered Metric Spaces - Dewangan, Vinita; Banerjee, Amitabh; Koushik, Pushpa (Communications in Mathematics and Applications, 2018)
In this paper, we obtain coupled best proximity point theorems for generalized contraction in partially ordered metric spaces using P-operator technique. The results presented in this paper generalize and improve some known results in the literature.